ANALISIS SETSUBIJI SEI DAN PADANANNYA DALAM BAHASA INDONESIA (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
This study aims to determine the class classification of words, grammatical meaning, syntactic functions and Indonesian equivalent of the suffix sei. In analyzing word class classifications, using the referential equivalent method. The method of data analysis in grammatical analysis is the aggregate method, with advanced techniques of fade. Whereas in the equivalent analysis, using the method of compounding analysis. The results of this study are: Class words that can be attached to the -sei namely, denominal verbs/ doumeishi of type, action verbs/dousa, state verbs/ joutai and verbs of change/ henka, then denominal adjectives/keiyoudoushi which expressing characters and feelings. Then, nouns/ meishi type of person/hito, object/mono, situation /jitai, and time/ jikan. -Sei also changes word classes to abstract nouns. -Sei in Indonesian, can be added as a suffix -itas, -si / i, -nya, -if and confix ke- an, or can also change words such as adding meaning to power/character, and change meaning into risk, base, and scientific.The grammatical meaning produced by the -sei is, increasing levels, changing meanings (reform - innovation, anticipation - vision, elastic - flexible), adding the meaning of 'power' and 'character', changing the meaning nuance, adding to the impression of feeling, and adding to the subjective / objective impression.